The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1039/c7nr08001h
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative characterization of the ionic mobility and concentration in Li-battery cathodes via low frequency electrochemical strain microscopy

Abstract: Electrochemical strain microscopy (ESM) can provide useful information on the ionic processes in materials at the local scale. This is especially important for ever growing applications of Li-batteries whose performance is limited by the intrinsic and extrinsic degradation. However, the ESM method used so far has been only qualitative due to multiple contributions to the apparent ESM signal. In this work, we provide a viable approach for the local probing of ionic concentration and diffusion coefficients based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 45 publications
5
42
0
Order By: Relevance
“…Spatially resolved imaging of these shifts reveals an inhomogeneity of the lithiated phase in the middle of the particles, producing a core structure, while shell is enriched by lithium ( Figure 2). This observation is in line with recent electrochemical strain microscopy measurements in the same material [14]. the delithiated samples we also observed Raman band around of 680-690 cm −1 , which cannot be related to LMO vibration modes.…”
Section: Characterization Of Lithiated Statesupporting
confidence: 93%
See 1 more Smart Citation
“…Spatially resolved imaging of these shifts reveals an inhomogeneity of the lithiated phase in the middle of the particles, producing a core structure, while shell is enriched by lithium ( Figure 2). This observation is in line with recent electrochemical strain microscopy measurements in the same material [14]. the delithiated samples we also observed Raman band around of 680-690 cm −1 , which cannot be related to LMO vibration modes.…”
Section: Characterization Of Lithiated Statesupporting
confidence: 93%
“…Spatially resolved imaging of these shifts reveals an inhomogeneity of the lithiated phase in the middle of the particles, producing a core structure, while shell is enriched by lithium ( Figure 2). This observation is in line with recent electrochemical strain microscopy measurements in the same material [14]. Though Raman band position can be used as a signature of the lithiation state, the accuracy of this approach is not very high due to the apparent difficulties in the precise evaluation of the peak positions in complex Raman spectra with many overlapped peaks.…”
Section: Characterization Of Lithiated Statesupporting
confidence: 85%
“…66 Resonance tracking techniques allow the determination of the driving force or strain in PFM/ESM by accounting for any change in the contact resonance frequency or quality factor, analyzed in terms of the simple harmonic oscillator (SHO). With few exceptions 32 71 , and tall tips. 25 Often, however, the tip-sample stiffness required to eliminate electrostatic effects is sufficiently large to compromises the material, particularly important for fragile thin films or biological materials.…”
Section: Potential Artifacts In Vm-afmmentioning
confidence: 99%
“…Therefore, ferroelectriclike hysteresis loops can be formed in non-ferroelectric materials, such as LiCoO 2 and lithium-ion conductors. [104][105][106][107][108] These results revealed that it is likely to misinterpret the ionically mediated PFM hysteresis loop as ferroelectricity. Accordingly, several studies have distinguished these aspects from each other based on voltage conditions, harmonic responses, and environmental conditions.…”
Section: Non-piezoelectric Contributions To the Pfm Signalmentioning
confidence: 99%